Canavalia ensiformis Protein Extract Effect Toward Serum Lipid Profile of Hypercholesterolemic Sprague Dawley Rat (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Riskesdas 2013 showed the prevalence of abnormal total cholesterol levels in Indonesia is 35.9%, low HDL cholesterol is 22.9%, high LDL cholesterol is 15.9%, and high triglyceride is 11.9%. This study aimed to prove the effect of jack bean protein extract toward serum lipid profile of a hypercholesterolemic rat. This was a true experimental study conducted in September 2016 with post-only control group design. Twenty four male Sprague Dawley rats were randomly classified into 4 different groups; control negative group (C-), control positive group (C+), first experimental group (X1) which was given jack bean extract 4g/200g of body weight of the rat per day, and second experimental group (X2) which was given jack bean extracts 6g/200g of body weight of the rat per day. Treatment for 2 weeks showed a significant effect. Total cholesterol, LDL cholesterol, and triglycerides levels of groups with protein jack bean extract administration were lower than the positive control group (p 0.05). Increasing doses of jack bean extracts was linear with serum lipid profile improvement of Sprague Dawley Rat. These result indicated the positive effect of jack bean protein extract toward serum lipid profile of hypercholesterolemic Sprague Dawley Rat.